The role of political institutions for the effectiveness of central bank independence - Kai Hielscher; Gunther Markwardt (Center for Economic Studies and ifo Institute (CESifo), 2011)
This paper empirically studies the impact of the quality of political institutions on the link between central bank independence and inflation. Making use of data on the evolution of central bank independence over time and controlling for possible nonlinearities, we employ interaction models to identify the conditions under which more central bank independence will enhance a country's inflation performance. Examining a cross-section of up to 69 countries, we are able to show that granting a central bank more autonomy does not necessarily lead to better inflation performance. To lower inflation by increasing independence, two conditions must be fulfilled: (1) The change in independence must be sufficiently large, and (2) the quality of the political institutions must be sufficiently high.
Keywords: E58; E02; E31; 330; central bank independence; inflation; institutional quality; monetary policy; Inflation; Geldpolitik; Zentralbankautonomie; Institutionelle Infrastruktur; Politische Stabilität; Schätzung; Welt